The E3 Ubiquitin Ligase HectD1 Suppresses EMT and Metastasis by Targeting the +TIP ACF7 for Degradation - Stéphanie Duhamel; Marie-Anne Goyette; Marie-Pier Thibault; Dominic Filion; Louis Gaboury; Jean-François Côté (Cell Reports, 2018)
Cancer cells exploit the epithelial-to-mesenchymal transition (EMT) program to become metastatic. Cytoskeletal regulators are required in mesenchymal cells where they promote EMT and EMT-induced migration. In a search for regulators of metastasis, we conducted shRNA screens targeting the microtubule plus-end tracking proteins (+TIPs). We show that the +TIP ACF7 is essential both for the maintenance of the EMT program and to promote migration. We find that the E3 ubiquitin ligase HectD1 promotes ACF7-proteasome-mediated degradation. Depletion of HectD1 stabilized ACF7, and this enhanced EMT and migration. Decreased HectD1 expression increased metastases in mouse models and conferred increased resistance to the cytotoxic drug cisplatin. A retrospective analysis of biopsies from breast cancer patients also reveals a correlation between higher ACF7 or lower HectD1 expression with poor clinical outcomes. Together, these results suggest that the control of ACF7 levels by HectD1 modulates EMT and the efficiency of metastasis.